Síntese de novos selenofenos indólicos via adição eletrofílica de SeCl2 - Martins, Guilherme Ariel Machado (2019)
This work initially describes a novel and efficient protocol for the synthesis of 3-selenophen-3-yl-1H-indole derivatives via the electrophilic addition of SeCl2 to the conveniently substituted propargyl-indoles. The synthetic route involved an initial migration of the indole group, caused by the electrophilic addition of SeCl2 to the triple bond of propargyl indole, through the 1-seleno-1,3-diene intermediate, followed by cyclization and formation of the respective selenophene nucleus. The reaction occurs at room temperature in very good yields, showing excellent selectivity, broad substrate scope and wide tolerance to functional groups. In a second part, an easy and convenient route was developed for the synthesis of selenofen[2,3-b]indole derivatives via the electrophilic addition of SeCl2 to the appropriately substituted 3-(alkyl-ethynyl)-1H-indoles. The reaction scope was systematically evaluated, and the products containing the selenophenic ring fused to the indole were obtained in moderate to very good yields. The performance of the transformation was affected by steric and electronic properties of the substituent attached to the nitrogen atom of the indole moiety of the starting material and to a lesser extent by the nature and position of the substituents at the aryl moiety. In addition to the synthesis, it was evaluated the antifungal and antibacterial activities of the obtained products.